A study of the organization and functions of parent-teacher associations in selected public secondary schools in Manila and Quezon City its implication to parent-teacher associations in Bangkok, Thailand - Soysonthi, Sermsook 1940- ([Quezon City s.n.], 1967)
The study analyzed the organization and functions of parent-teacher associations in twenty selected public secondary schools in Manila and Quezon City with the aim of deducing implications to the parent-teacher associations in Bangkok, Thailand.
Thesis (M.Ed.)--University of the Philippines
Keywords: Parents' and teachers' associations